TRADISI PERAWATAN ORANG TUA OLEH ANAK PEREMPUAN BUNGSU: DAMPAKNYA TERHADAP PEMBAGIAN WARISAN DI DESA SUNGAI TONANG - Ghufron, Muhammad Rojil (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research aims to examine the influence of the tradition of caring for parents by the youngest daughter on the practice of inheritance distribution in Sungai Tonang Village. In this context, the division of inheritance does not always follow the textual provisions of Islamic law, but is influenced by local values that live and develop in the community. This research uses a field research method with a legal anthropology approach to examine the law not only as a written norm, but also as a social practice that is accepted and carried out by the community. The data sources obtained are primary data obtained through direct interviews with traditional leaders and local families while secondary data comes from related literature, such as books and scientific journals. The results show that the youngest daughter in Sungai Tonang Village often gets a larger share of inheritance than other heirs such as houses or land, as a form of appreciation for their role in caring for their parents in old age. This decision is motivated by emotional closeness, social responsibility, and the economic condition of the youngest daughter who is considered not fully independent. The contribution of this research lies in revealing the local dynamics in inheritance distribution that emphasizes the value of family devotion and responsibility, as well as showing the importance of legal flexibility in responding to the socio-cultural needs of the community.